Technical Note on Preparing the National Territorial and Spatial Plan of China - World Bank Group (World Bank, Washington, DC, 2020)
China’s recently established Ministry of Natural Resources (MNR) has been given the task of developing the country’s first National Territorial and Spatial Plan (NTSP). This Plan will replace four separate sectoral plans previously prepared by different ministries. The NTSP is meant to integrate the sectoral plans and address the overlaps, disconnects, and conflicts among them. The goal is to have ‘One Plan’ for China. This Advisory Note responds to a request from MNR to provide policy advice and lessons drawn from international practices on topics relevant to the Territorial and Spatial Plan.